Turkey's Nationalist Action Party ideas and practices - Opçin-Kıdal, Arzu (Routledge studies in Middle Eastern politics, 2025)
"This book provides a comprehensive analysis of the nationalist ideas and practices of Turkey's Nationalist Action Party (MHP) over the course of several decades, from the leadership of its founder, Alparslan Türkeş, to Devlet Bahçeli. Applying both diachronic and synchronic approaches to the multidimensionality of nationalism, the book analyzes how Türkeş and Bahçeli emphasized or de-emphasized ethnic, cultural, and civic components of the party's nationalism in response to the threats they perceived in specific historical contexts. The author draws on party documents, speeches, and interviews to examine how recurring themes in Türkeş's and Bahçeli's nationalist ideas and practices have evolved over half a century, between 1965 and 2015. In this way, the book provides fresh insights into the evolution and complexity of the MHP's nationalism, thereby contributing to the theoretical understanding of nationalism's multidimensionality. The book also highlights the political significance of the MHP in contemporary Turkey, where nationalist and right-wing politics have become increasingly influential in recent years. Spanning a number of disciplines, including political science, international relations, and Turkish studies, the book will be of interest to a broad range of scholars and students, as well as those seeking insights into the broader implications of nationalism."